State Ownership and Firm Innovation in China: An Integrated View of Institutional and Efficiency Logics - Zhou, Kevin Zheng; Gao, Gerald Yong; Zhao, Hongxin (Administrative science quarterly, 2017)
Using two longitudinal panel datasets of Chinese manufacturing firms, we assess whether state ownership benefits or impedes firms' innovation. We show that state ownership in an emerging economy enables a firm to obtain crucial R& D resources but makes the firm less efficient in using those resources to generate innovation, and we find that a minority state ownership is an optimal structure for innovation development in this context. Moreover, the inefficiency of state ownership in transforming R& D input into innovation output decreases when industrial competition is high, as well as for start-up firms. Our findings integrate the efficiency logic (agency theory), which views state ownership as detrimental to innovation, and institutional logic, which notes that governments in emerging economies have critical influences on regulatory policies and control over scarce resources. We discuss the implications of these findings for research on state ownership and firm innovation in emerging economies.